Kreasi Bahan Baku Penggunaan Tahu Sebagai Pengganti Cream Cheese Dalam Pembuatan Makanan Penutup (Olahan Egg Tart dan Cheesecake) - Febryola Indra; Kyani Pindy; Livia Imelda; Juliana Juliana; Sherla Valensky (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
In the food industry, innovation continues to be the key to meeting diverse market demands and enhancing product value. One intriguing alternative is the use of tofu as a substitute for cream cheese in desserts, given that tofu is rich in protein, has a texture similar to cream cheese, and can be processed into various shapes and flavors. This research aims to (1) explore the research findings regarding the use of tofu as a creation in the preparation of dessert dishes, specifically egg tart and cheesecake, (2) evaluate how the utilization of tofu affects the sensory characteristics, texture, taste, and aroma of the egg tart and cheesecake desserts, (3) determine whether the use of tofu results in a more affordable cost compared to using cream cheese. The research employs a quantitative research method utilizing experimental techniques and purposive sampling questionnaire methods. The results of this research indicate that the use of tofu as an innovation in dessert preparation holds significant potential. These findings provide support for the development of the idea that the use of tofu can be considered an innovative and value-added raw material in the creation of egg tart and cheesecake.